Nonlinear Photonics Using Low‐Dimensional Metal‐Halide Perovskites: Recent Advances and Future Challenges. Issue 11 (4th February 2021) - Chen, Weiqiang; Zhang, Feng; Wang, Cong; Jia, Mingshuang; Zhao, Xinghang; Liu, Zhaoran; Ge, Yanqi; Zhang, Yupeng; Zhang, Han
Abstract: Low‐dimensional metal‐halide perovskites have exhibited significantly superior nonlinear optical properties compared to traditional semiconductor counterparts, thanks to their peculiar physical and electronic structures. Their exceptional nonlinear optical characteristics make them excellent candidates for revolutionizing widespread applications. However, the research of nonlinear photonics based on low‐dimensional metal‐halide perovskites is in its infancy. There is a lack of comprehensive and in‐depth summary of this research realm. Here, the state‐of‐the‐art research progress related to third‐and higher‐order nonlinear optical properties of low‐dimensional metal‐halide perovskites with diverse crystal structures from 3D down to 0D, together with their practical applications, is summarized comprehensively. Critical discussions are offered on the fundamental mechanisms beneath their exceptional nonlinear optical performance from the physics viewpoint, attempting to disclose the role of intrinsic attributes (e.g., composition, bandgap, size, shape, and structure) and external modulation strategies (e.g., developing core–shell structures, transition metal ion doping, and hybridization with dielectric microspheres) in tuning the response. Additionally, their potential applications in nonlinear photonics, nonlinear optoelectronics, and biophotonics are systematically and thoroughly summed up and categorized. Lastly, insights into the current technical challenges and future research opportunities of nonlinear photonics based on low‐dimensional metal‐halide perovskites are provided. Abstract : Low‐dimensional metal‐halide perovskites have exhibited superior nonlinear optical properties compared to traditional semiconductor counterparts. A comprehensive and in‐depth summary of the state‐of‐the‐art research progress related to third‐ and higher‐order nonlinear optical properties of low‐dimensional metal‐halide perovskites with diverse crystal structures from 3D down to 0D, together with their widespread practical applications, is provided.